Orientasi Pembelajaran Dan Perilaku Kerja Inovatif (Peran Efikasi Diri Kreatif Pada UKM) - Noerchoidah - Noerchoidah; Nurdina Nurdina; Tri Ariprabowo (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2022)
Background – In the dynamic era of the business world, achieving business growth and sustainability requires human resources who have innovative skills. SMEs play an important role in the economic growth of a country. However, the added value provided is still not significant because the human resources owned by SMEs are still relatively low in innovative abilities. The solution is to conduct learning orientation and innovative behavior with the mediating role of creative self-efficacy. Objectives - To provide new insights about the innovative behavior of SMEs, the extent to which learning orientation for innovative activities and creative self-efficacy influence the innovative behavior of SMEs. Design/method/approach – This study uses quantitative methods. Respondent data was collected using a questionnaire. The sample used was 105 SMEs in Surabaya using the purposive sampling technique. Hypothesis testing using Partial Least Square (PLS). Findings - The results of this study that learning orientation has a significant effect on creative self-efficacy and innovative work behavior, creative self-efficacy has a significant effect on innovative work behavior. Furthermore, creative self-efficacy plays a role in mediating learning orientation and innovative work behavior. Research Implications - For business continuity to be maintained, SMEs must produce products that are different from competitors. SMEs must increase learning opportunities to produce highly innovative work behavior. Research Limitations - This study only involved SMEs in Surabaya so that future researchers should conduct similar research in a wider area for more comprehensive results.